Alternative policy narratives of the future of climate change : Analyzing Finland's energy and climate strategy and news reports - Parkkinen, Marjukka (Wiley, 2025)
In this article, we examine the ways in which the futures of climate change and the climate change policy process are constructed as narratives—both explicitly and implicitly—in two different yet interconnected contexts that shape public climate discourse and debate: foresight-based political decision-making and journalism. The featured case is the National Energy and Climate Strategy of Finland for 2030. We employ and expand the Narrative Policy Framework to better understand the co-existent, implicit narratives of the future in the contexts of policy and media. We construct two co-existing yet contradictory underlying narratives of the future of climate change and climate policy. Our approach reveals that the prevailing master narrative of a desirable future is challenged by a co-existing counter narrative where policies in the energy and climate strategy prioritize shorter-term policy interests over climate change. Building on these findings, we argue that, in climate policy communication, communicators convey futures through narratives—both explicitly, as descriptions of what is perceived, hoped, and anticipated to happen, and implicitly, as the sum of the parts included and excluded.